Relación entre estilos parentales y rendimiento académico en niños y adolescentes en etapa escolar - Castillo Herrera, Daniela del Rosario (2022)
What happens and is built inside the family is reflected in the other surroundings in which the child or adolescent interacts, such as in the educational field. The aim of this study is to identify if there is a relationship between parenting styles and academic performance in children and adolescents in school, through a systematic review of quantitative research with a correlational design, following the PRISMA guideline (Page et al., 2021). The following databases used were Ebsco, Scopus, APA PsycNET, Dialnet, ProQuest and Scielo. Studies that examined the relationship of both variables were selected (n=10). The research instruments that evaluate parenting styles have reliability; meanwhile, academic performance is based on grades. Democratic and authoritarian parenting styles contribute to better academic performance; whereas, permissive and neglectful parents make it difficult. It was identified that self-concept, self-regulation, self-efficacy and motivation are variables that significantly influence academic performance. Future studies should include larger testing samples as well as use appropriate research instruments with psychometric properties to measure academic achievement.